Sosialisasi Dan Pelatihan Penggunaan Aplikasi Augmented Reality Untuk Pemahaman Geometri Pada Guru Dan Siswa SMP Negeri 4 Percut Sei Tuan - Muhammad Rizky Mazaly; Sihotang, Siti Fatimah; Ria Dila Audiva; Retno Selvia (Jurnal Pengabdian Ahmad Yani, 2024)
Community service activities (PKM) were carried out in the form of training on the use of Augmented Reality applications for teachers and students for understanding geometry at SMP Negeri 4 Percut Sei Tuan. The number of participants in this community service activity amounted to 26 people. The purpose of this PKM activities include 1) to determine the use of Augmented Reality media in learning geometry on teachers and students of SMP Negeri 4 Percut Sei Tuan, and 2) to determine the response of students after participating in socialization and training on the use of Augmented Reality in learning geometry on students and teachers of SMP Negeri 4 Percut Sei Tuan. The method implemented in this PKM activity consists of four stages The fourth stage is the stage of evaluating activities. The first stage is the observation stage of the students and teachers. The second stage is the stage of providing training materials. The third stage is the stage of providing problems to be solved by students and teachers. Evaluation of PKM activities is carried out through questionnaires given to students and teachers after PKM activities are held. Data analysis is done quantitatively descriptive. The conclusions obtained are 1) the students and teachers have known how to use Augmented Reality applications in understanding geometry, and 2) the response of students and teachers in this activity is categorized as good.